Galaxy clustering in the VVV Near-IR Galaxy Catalogue - Soto, Mario (2022)
Mapping galaxies at low Galactic latitudes and determining their clustering status are fundamental steps in defining the large-scale structure in the nearby Universe. The VISTA Variables in the Vía Láctea (VVV) near-IR galaxy catalogue (VVV NIRGC) allows us to explore this region in great detail. Our goal is to identify galaxy overdensities and characterize galaxy clustering in the Zone of Avoidance. We use different clustering algorithms to identify galaxy overdensities: the Voronoi tessellations, the minimum spanning tree, and the ordering points to identify the clustering structure. We studied the membership, isolation, compactness, and flux limits to identify compact groups of galaxies. Each method identified a variety of galaxy systems across the Galactic plane that are publicly available. We also explore the probability that these systems are formed by concordant galaxies using mock catalogues. 19 galaxy systems were identified in all of the four methods. They have the highest probability to be real overdensities. We stress the need for spectroscopic follow-up observations to confirm and characterize these new structures.